Pengaruh Model Problem Based Learning (PBL) Terhadap Keterampilan Kolaborasi Peserta Didik pada Pembelajaran IPAS Kelas V Sekolah Dasar - Duana Dinda Saputri (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
21st century learning focuses on the skills needed to prepare learners to face future challenges, one of which is collaboration skills. Collaboration skills include the ability to work together in teams, share ideas, and solve problems together. The problem that occurs is that students still depend on the teacher's explanation so that learning is dominantly unidirectional. This causes the lack of learner contributions (passive) so that collaboration skills during learning become less than optimal. Based on these problems, an alternative solution is obtained, namely the use of the Problem Based Learning (PBL) model. The purpose of this study is to determine whether or not there is an effect of the PBL model on the collaboration skills of students in learning IPAS grade V elementary school. This type of research is quasi experimental with a non-equivalent control group design, two class samples used are class V A and V B through homogeneity test using saturated sample technique. Based on the results of the study, the tcount of 5,169 was obtained. The results were then consulted on the t-table with df = 48 at the 5% significance level obtained the t-table value of 2,010. The result of the t-test analysis shows that the value of tcount > ttable is 5,169>2,010, so it can be concluded that there is an effect of PBL model on students' collaboration skills in learning IPAS grade V elementary school.
Reaploud Repository April 2026
Keywords: Collaboration skilsl; Problem Based Learning; 21st century learning